HMGN2 and Histone H1.2: potential targets of a novel probiotic mixture for seasonal allergic rhinitis - Li, Lisha; Wen, Xueyi; Gong, Yiyi; Chen, Yuling; Xu, Jiatong; Sun, Jinlyu; Deng, Haiteng; Guan, Kai (Frontiers in Microbiology, 2023)
Background: Allergic rhinitis (AR) is a common nasal inflammatory disorder that severely affects individual’s quality of life (QoL) and poses heavy financial burdens. Besides routine treatments, probiotic intervention has emerged as a promising strategy in preventing and alleviating of allergic disease. The main objective of this study was to determine the effect of a novel multi-strain probiotic mixture on AR symptoms and investigate potential targets underlying the probiotic intervention. Methods: A randomized, double-blind, placebo-controlled clinical study was conducted in AR patients allergic to autumnal pollens (n = 31). Placebo or a novel probiotic mixture, composing Lactobacillus. rhamnosus (L. rhamnosus) HN001, L. acidophilus NCFM, Bifidobacterium. lactis (B. lactis) Bi-07, L. paracasei LPC-37, and L. reuteri LE16, was administered lasting 2 months. The therapeutic efficacy was evaluated by symptom assessment scale. Before and during the pollen season, blood samples were collected and PBMCs were isolated for further tandem mass tags (TMTs)-based quantitative proteomic analyses. Potential targets and underlying pathways were explored using bioinformatic methods. Results: During the pollen season, the rhinoconjunctivitis symptom score of participants administrated probiotics (probiotic group, n = 15) was significantly lower than those administrated placebo (placebo group, n = 15) (P = 0.037). The proteomic analyses identified 60 differentially expressed proteins (DEPs) in placebo group and subsequent enrichment analyses enriched a series of pathways, including inflammation pathways, coagulation cascade, lipid, carbohydrate and amino acid metabolic pathways, transcription, and translation processes. Least Absolute Shrinkage and Selection Operator (LASSO) regression extracted five main elements, that is GSTO1, ATP2A2, MCM7, PROS1, TRIM58, as signature proteins. A total of 17 DEPs were identified in probiotic group and there was no pathway enriched. Comparison of DEPs in two groups revealed that expression levels of high mobility group nucleosome-binding domain-containing protein 2 (HMGN2) and Histone H1.2 presented an opposite trend with different interventions. Conclusion: Our data showed that AR symptoms alleviated after treatment with the novel multi-strain probiotic mixture, and the proteomic analyses suggested that HMGN2 and Histone H1.2 might be targets of probiotic intervention for seasonal AR.